An Analysis of Interlanguage Performed by Students of an Islamic Boarding School in Tasikmalaya - aziez, feisal (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2016)
This descriptive study aims at: (1) finding out and describe the phonological,lexical,  and  syntactic  forms  of  English  language  learners’  inter language,  and  (2)finding out whether there are any differences in the inter language of the learners ofdifferent grades. The subjects of this research were 24 learners of the first, second,and third  grade  of  an  Islamic  boarding  school  in  Tasikmalaya.  The  data  werecollected  from  students’  conversations,  interviews,  and  reading  aloud.  The  datawere  recorded  and  transcribed.  Then,  the  data  were  filtered  by  using  Corder’sprocedure. The results of the research reveal the existence of the following aspectsin the learners’ inter language: (1) phonological transfers, (2) lexical transfers, (3)syntactic  transfers,  (4)  phonological  overgeneralizations,  (5)  lexicalovergeneralizations, and (6) syntactic overgeneralizations. This research also foundout some differences in the inter language of the students of different grades.